Integrasi Berbasis Sistem antara Rekayasa Operasi, Manajemen, dan MSDM untuk Kinerja Industri Berkelanjutan - Abdurrozzaq Hasibuan; Rusli Yusuf; Suhela Putri Nasution (JiTEKH, 2025)
Industrial organizations are currently operating in increasingly complex environments characterized by high levels of uncertainty, rapid technological advancement, and growing sustainability pressures. Under these conditions, improvements in industrial performance can no longer be effectively achieved through isolated technical or managerial approaches. This study aims to develop a systems-based framework that integrates operations engineering, management systems, and human resource management (HRM) to support sustainable industrial performance using a System Dynamics approach. The research methodology is systematically structured, encompassing problem formulation, system boundary definition, causal loop diagram development, stock-flow modeling, model validation, and policy scenario simulation. Simulation results indicate that fragmented strategies generate only limited short-term performance improvements. In the baseline scenario, the Sustainable Industrial Performance Index increases from 70.0 to 70.9 within a two-month period. An HRM-focused strategy raises the index to 71.9, while an operations-oriented strategy achieves a higher improvement, reaching 72.8. The most substantial improvement is observed under an integrated policy scenario that combines HRM investment, enhanced operational reliability, and managerial alignment, resulting in an index increase to 73.8 over the same period. These findings confirm that integrated policies create synergistic effects and highlight the critical role of feedback mechanisms and time delays in shaping industrial performance dynamics. This study concludes that sustainable industrial performance emerges from the dynamic interaction among technical, managerial, and human subsystems and provides both theoretical contributions to industrial systems modeling and practical value as a decision-support foundation for strategic policymaking.